Investigation of the diabetic patients’ knowledge on diabetes and the role of clinical pharmacist in providing pharmaceutical care to them - Taner, Neda; Tatlıpınar, Mücteba Eşref; Aydın, Ayşe Nur; Omurtag, Gülden Zehra (İstanbul Medipol University, 2020)
Type 2 Diabetes is a common incurable metabolic disorder with worldwide increasing prevalence. International Diabetic Association noticed that there is a very fast and alarming increase in the worldwide prevalence of Diabetes. In 2012, diabetic popu-lation around the world has reached 371 million people. Untreated or undertreated Type 2 Diabetes does affect the quality of life of the patients both directly by symp-toms and indirectly by short term and long-term complications. In addition to the direct effects of type 2 diabetes mellitus, affects the patient’s life in a bad way, if the treatment process is not followed carefully, the quality of life of the patient will be re-duced. At this point, clinical pharmacist has an extremely important role in determin-ing and executing the correct clinical treatment. Besides that, the importance of the patient’s level of knowledge about the disease and its impact on the treatment process is very important. The major goal of this thesis is evaluating the diabetic patients` knowledge on diabetes and the effect of this point on treatment process. This study has been done in Merve Pharmacy of Muğla/Turkey between January and March of 2018. A questionnaire consisting of 20 multiple choice questions has been used to evaluate 50 participants who are clinically diagnosed diabetics. SPSS 23.0 statistical program was used for the statistical analysis of the data and the findings were evaluated at and 5% significance level. It has been statistically observed that knowledge levels of patients affected the treatment process. Recognizing the importance of this factor by clinical pharmacists and other health professionals will increase the training for diabetes and prevent the problems arising from the patient’s low-level knowledge.
Keywords: Clinical Pharmacy; Disease Knowledge; Type 2 Diabetes